Peningkatan Kepatuhan Protokol Penanganan Kasus Covid-19 melalui Edukasi Pengetahuan, Pembentukan Sikap, dan Pengawasan di Layanan Medis Darurat X Kuwait - Reskadarto, Nanang; Ariyani, Nafiah; Ramli, Soehatman (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: This community service aims to enhance compliance with Covid-19 handling protocols among medical staff at the Kuwait Emergency Medical Services (EMS) by improving knowledge, attitudes, and supervision. Methodology: The service was conducted at the Kuwait EMS using a quantitative cross-sectional approach. Data were collected from 104 medical staff members using structured surveys. The analysis was performed using SEM-PLS software to evaluate the relationships between knowledge, attitudes, supervision, and compliance levels. Results: The results of this service indicate a positive and significant relationship between knowledge, attitudes, and supervision and the level of compliance with Covid-19 protocols among medical staff. Limitations: This service is limited by its cross-sectional design, which restricts its ability to infer causality. Contribution: This service provides valuable insights into how improving knowledge, attitudes, and supervision can enhance compliance with the protocols. The findings offer practical implications for health institutions seeking to strengthen their Covid-19 response strategies and improve overall safety in medical settings while also making a positive contribution to the community.